Minnesang trifft Pijjut und Midrasch. 'Josef ha-zadik' und die jüdische Rezeption der deutschsprachigen höfischen Literatur - Hon, Jan (Beiträge zur Geschichte der deutschen Sprache und Literatur, 2023)
The essay examines the fourteenth-century Yiddish poem Yosef Ha-Tsadik about Joseph and Potiphar's wife. The poem, presented here in a new critical edition, is primarily based on Hebrew and Aramaic midrashic and liturgical sources but also incorporates elements derived from German courtly love poetry, mainly to express Potiphar's wife's advances toward Joseph. It can thus be read as a Jewish dialogue with Christian secular literary traditions. Drawing on a comparison with the Jewish pretexts – some of which are presented here for the first time in German translations – and a number of examples from Minnesang, the study analyzes the strategies of both participation in and (ironic) distancing from the Christian courtly discourse.
CRIS-Team Scopus Importer:2023-12-15